The Impact of Green Finance, FinTech and Digital Economy on Environmental Sustainability: Evidence from Advanced Panel Techniques - Ibrahim, Abdulhadi; Almasria, Nashat Ali; Almaqtari, Faozi A.; Al-Kasasbeh, Omar; Alhatabat, Zaidoon; Ershaid, Diala (International Journal of Energy Economics and Policy, 2024)
Improving environmental sustainability is a crucial priority for economies to further global progress. The United Nations General Assembly has proposed enhancing environmental sustainability by adopting the SDG-7 recommendations. This study investigates the effect of green finance, fintech and digital economy on environmental sustainability utilizing panel data between 2013 and 2023 in Middle Eastern countries: Saudi Arabia, Turkey, Kuwait, United Arab Emirates and Qatar. For the analysis, panel unit root test, panel cointegration test and Pairwise Dumitrescu-Hurlin panel Causality tests were done. Our empirical results show that cointegration is among the variables that were analyzed. Green finance, digital economy, and FinTech are closely interrelated. The outcomes may provide helpful knowledge regarding the development of environmental sustainability. Policymakers are recommended to formulate feasible and energy system-compatible policies to provide green funding to the energy systems of Middle Eastern countries with maximum convenience.